2003
DOI: 10.1007/s00125-003-1145-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of urotensin II gene in genetic susceptibility to Type 2 diabetes mellitus in Japanese subjects

Abstract: Aim/Hypothesis. Urotensin II is a potent vasoactive hormone and the urotensin II gene (UTS2) is localized to 1p36-p32, one of the regions reported to show possible linkage with Type 2 diabetes in Japanese subjects. The aim of this study is to investigate a possible contribution of SNPs in the UTS2 gene to the development of Type 2 diabetes. Methods. We surveyed SNPs in the UTS2 gene in 152 Japanese subjects with Type 2 diabetes mellitus and two control Japanese cohorts: one consisting of 122 elderly subjects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 18 publications
3
42
0
Order By: Relevance
“…In the Japanese population, the S89N polymorphism in the UTS2 gene was found to be associated with the development of type 2 diabetes (141). The allele frequency of 89N was greater in type 2 diabetics; and in the subjects with normal glucose tolerance, 89N was correlated to higher insulin levels during oral glucose tolerance testing (141).…”
Section: Pathological Significance Of Uiimentioning
confidence: 87%
“…In the Japanese population, the S89N polymorphism in the UTS2 gene was found to be associated with the development of type 2 diabetes (141). The allele frequency of 89N was greater in type 2 diabetics; and in the subjects with normal glucose tolerance, 89N was correlated to higher insulin levels during oral glucose tolerance testing (141).…”
Section: Pathological Significance Of Uiimentioning
confidence: 87%
“…Consistent with the widespread distribution of UT, it has been shown that UII exerts a number of biologic effects including regulation of behaviors and neuroendocrine activities, as well as central and peripheral control of blood pressure and heart rate Vaudry et al, 2010). Clinical studies have provided evidence that UII and UT are implicated in various pathologies, including cardiovascular diseases Ng et al, 2002;Richards et al, 2002;You et al, 2012;Watson et al, 2013), renal diseases , and diabetes (Wenyi et al, 2003;Sidharta et al, 2009). The various activities of UII and the potential implication of the urotensinergic system in various pathologies have prompted academic laboratories and pharmaceutical companies to design specific agonists and antagonists that are currently used for basic research and may lead to therapeutic applications Maryanoff and Kinney, 2010;Tsoukas et al, 2011;Merlino et al, 2013).…”
Section: Introductionmentioning
confidence: 91%
“…Genetic studies have shown that single nucleotide polymorphisms (SNPs) in the UII gene are associated with type 2 diabetes mellitus (T2DM) in the Northern Chinese (Sun et al, 2002, Zhu et al, 2002Tan et al, 2006), Hong Kong Chinese (Ong et al, 2006), Japanese (Wenyi et al, 2003;Suzuki et al, 2004), Turkish (Okumus et al, 2012), and Spanish populations (Sáez et al, 2011). In particular, the SNP 3836C→T (S89N) found in the Japanese and Hong Kong populations has been associated with elevated plasma UII level, higher plasma insulin, insulin resistance, and susceptibility of developing T2DM (Wenyi et al, 2003;Suzuki et al, 2004;Ong et al, 2006). SNPs have also been reported in the UT promoter in the Japanese population, but no significant association with T2DM was found (Suzuki et al, 2004).…”
Section: E Effect Of Urotensin Ii/urotensin Ii-related Peptide On Thmentioning
confidence: 99%
“…The U-II system is up-regulated in diabetes mellitus; plasma U-II levels are increased in type 2 diabetic patients and further increased by renal failure (Totsune et al, 2003(Totsune et al, , 2004; the S89N polymorphism in the U-II gene is associated with the development of insulin resistance and type 2 diabetes (Wenyi et al, 2003); U-II immunoreactivity is also increased in atherosclerotic vessels (Maguire et al, 2004); and finally, there is a dramatic overexpression of UT receptors in kidneys of diabetic patients, particularly in the tubular epithelium of dilated or damaged tubules, suggesting a direct role in the tubular toxicity of proteins (Langham et al, 2004). The differential expression of U-II and UT receptors in normal physiology and the pathological situation of diabetes suggest a contribution of the endogenous U-II system to the disease.…”
mentioning
confidence: 99%